ChemInform Abstract: Chiral Organic Contact Ion Pairs in Metal‐Free Catalytic Enantioselective Oxidative Cross‐Dehydrogenative Coupling of Tertiary Amines to Ketones. Issue 45 (14th October 2013) - Zhang, Gen; Ma, Yunxia; Wang, Shoulei; Kong, Weidong; Wang, Rui
Abstract This novel, efficient, and environmentally friendly title reaction affords tetrahydroisoquinoline derivatives from simple starting materials and under mild conditions in satisfactory yields with good diastereo‐ and enantioselectivities.